PENGENALAN HUBUNGAN KERJA DAN PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL KEPADA SISWA - Adiyaryani, N. N.; Putra, I.P. R.A.; Sudiarawan, K. A.; Darmadi, A.A. N.Y.; Sugama, D. G.D. (Buletin Udayana Mengabdi; Vol 21 No 1 (2022): Buletin Udayana Mengabdi, 2022)
The purpose of this dedication was to provide understanding to students who are prospective workers at Vocational High Schools in the field of tourism-related to work relations, disputes, and dispute resolution mechanisms within the scope of Indonesian labor law. This dedication was taken at the Dalung Tourism Vocational High School which targets students as prospective workers. With the onset of the Covid-19 pandemic, companies took strategic policies to deal with the pandemic which had direct implications for the rights of workers in an employment relationship. The lack of knowledge of Dalung Tourism Vocational High School students regarding legal basics related to employment makes it necessary to provide socialization and understanding of work relations, types of disputes, and settlement mechanisms. This dedication has come to the conclusion that the implementation of socialization and counseling provided has provided knowledge for students regarding work relations, disputes, and dispute resolution mechanisms in order to prepare themselves for the world of work.   Keywords: Socialization, Employment Relations, Disputes, Industrial Relations Disputes Settlement